Job satisfaction is driven by paternalistic leadership styles and work stress through motivation - Gilang Pratama Putra (Institute of Computer Science (IOCS), 2023)
Employees of PT Bank Rakyat Indonesia (Persero) Tbk in the Medan area are currently experiencing various complaints that can affect job satisfaction such as the lack of attention of the leadership to the needs of employees who can motivate employees in carrying out their duties, then the lack of guidance from the leadership towards employees in carrying out their daily duties, and the lack of motivation of employees in carrying out the tasks charged to them, and the employee's lack of sense of responsibility for their work. For this reason, the purpose of this study is to test the influence of paternalistic leadership style and work stress on job satisfaction through motivation as a variable intervening for employees of the Bank BRI Medan Regional Office. The method used in this study was a quantitative method with a total sample of 184 respondents. By using the PLS SEM (Partial Least Square-Structural Equation Model) data analysis technique, the results were obtained, namely paternalistic leadership style has a positive and significant effect on motivation, work stress has a negative and significant effect on motivation, paternalistic leadership style has a positive and significant effect on job satisfaction, work stress has no effect on job satisfaction, motivation has a positive and significant effect on job satisfaction, Paternalistic leadership style has a positive and significant effect on work satisfaction through motivation and work stress has a positive and significant effect on work satisfaction through employee motivation